GENETIC ANALYSIS OF MILK YIELD AND LACTATION PERIOD OF SHAMI GOATS RAISED IN MIDDLE OF IRAQ - Al-Azzawi, Salih Hassan (Diyala Agricultural Sciences Journal, 2017)
This study was conducted to evaluate productivity of Shami goats raised at the Ruminate Research station (Abo Gharib 20 km North West of Baghdad). A total of 450 milk records of Shami goats were collected during the years 2009-2011. These records were used to investigate the effect of some genetic and non-genetic factors (parity, month of birth, presence of horns and years of birth) on total milk yield (TMY) and lactation period (LP) produced by 250 Shami goats and 35 buck. The aim of this investigation was to measure the genetic ability of goats and bucks after the adjusted of fixed effect parity, month of birth, type of birth sex, presence of horns and years of birth). General Linear Model (GLM) procedure was used to study the effect of nongenetics factors. Restricted Maximum Likelihood (REML) method was employed to determine the variance components of the random effects using mixed model. To measure genetic parameters and to evaluate animal for the TMP and LP (estimate the Best Linear Unbiased Prediction, BLUP). The overall means of TMP and LP were 178.57 kg and 174.08 day respectively. The effect of parity season and year of parturition on the TMP and LP was significant. The heritability of the TMP and LP were 0.38 and 0.31 respectively. Positive and significant genetic and phenotypic correlations between TMY and LP (0.79 and 0.85 respectively) were noticed. The wide range in estimate of BLUP values of bucks (-22.35 to 27.52 kg) for TMY (-14.83 to 21.84) for LP and for dose range were (-30.16 to 41.87) TMY and (-15.74 to 17.95) LP in this study were recorded depending on TMY and LP which indicate genetic additive variance in this traits in selection programs.